Longitudinal evaluations of somatosensory-motor inhibition in Dopa-responsive dystonia. (February 2022) - Weissbach, Anne; Steinmeier, Annika; Pauly, Martje; Al-Shorafat, Duha M.; Saranza, Gerard; Lang, Anthony; Brüggemann, Norbert; Tadic, Vera; Klein, Christine; Münchau, Alexander; Bäumer, Tobias; Brown, Matt J.N.
Abstract: Introduction: GCH1 mutations have been linked to decreased striatal dopamine and development of dopa-responsive dystonia (DRD) and Parkinsonism. Sensory and sensorimotor integration impairments have been documented in various forms of dystonia. DRD patients with confirmed GCH1 mutations have demonstrated normal short-latency afferent inhibition (SAI), a measure of sensorimotor inhibition, under chronic dopaminergic replacement therapy (DRT), but reduced inhibition after a single l -dopa dose following 24 h withdrawal. Studies have revealed normal SAI in other forms of dystonia but reductions with DRT in Parkinson's disease. Longitudinal changes in sensorimotor inhibition are unknown. Methods: We analyzed sensorimotor inhibition using two different measures: SAI and somatosensory-motor inhibition using dual-site transcranial magnetic stimulation (ds-TMS). SAI was measured using digit stimulation 25 ms prior to contralateral primary motor cortex (M1) TMS. DS-TMS was measured using TMS over the somatosensory cortex 1 or 2.5 ms prior to ipsilateral M1 stimulation. A total of 20 GCH1 mutation carriers and 20 age-matched controls were included in the study. SAI and ds-TMS were evaluated in GCH1 mutation carriers both OFF and ON DRT compared to controls. Furthermore, longitudinal changes of SAI were examined in a subset of the same individuals that were measured ∼five years earlier. Results: Neither SAI nor ds-TMS were significantly different in GCH1 mutation carriers relative to controls. No effects of DRT on SAI or ds-TMS were seen but SAI decreased over time in mutation carriers OFF DRT. Conclusion: Our longitudinal results suggest changes in SAI that could be associated with plasticity changes in sensorimotor networks. Highlights: Reductions in SAI observed in DRD OFF over time. No differences in SAI or somatosensory-motor inhibition with ds-TMS in GCH1 mutation carriers. Dopaminergic treatment had no effects on SAI or ds-TMS.